2016
DOI: 10.1039/c5ra25053f
|View full text |Cite
|
Sign up to set email alerts
|

The influence of putrescine on the structure, enzyme activity and stability of α-chymotrypsin

Abstract: Information on protein stability is essential to study protein structure, activity, and interactions with ligands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…It is folded into two domains along with three intrachain and two interchain disulfide bonds. 35,41,42 In the case of native CT, far-UV CD spectra is characterized by two negative bands at 230 and 203 nm as shown in Figure 3. The shallow band ∼230 nm is intact in the presence of both the DESs along with demonstrating increased negative ellipticity.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…It is folded into two domains along with three intrachain and two interchain disulfide bonds. 35,41,42 In the case of native CT, far-UV CD spectra is characterized by two negative bands at 230 and 203 nm as shown in Figure 3. The shallow band ∼230 nm is intact in the presence of both the DESs along with demonstrating increased negative ellipticity.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
“…The band for Phe is usually weaker than Trp and Tyr; thus, it often escapes recognition. 35 Since the microenvironment of each amino acid is different, analysis of the near-UV CD spectrum is a complex task. Thus, for the sake of simplicity, herein, we have principally focused on peaks around 270−310 nm characteristic of Trp and Try.…”
Section: Acs Sustainable Chemistry and Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…It contains eight tryptophan (Trp) residues, four of which (Trp 237, Trp 215, Trp 207, and Trp 172) are exposed to the solvent. Whereas, two of them (Trp 29 and Trp 27) are moderately exposed to the solvent and two (Trp l41 and Trp 5l) are entirely buried inside the hydrophobic core. α-CT possesses unique structural and functional features for exploring the mechanism of protein folding and unfolding in different cosolvents …”
Section: Introductionmentioning
confidence: 99%
“…38−40 α-CT possesses unique structural and functional features for exploring the mechanism of protein folding and unfolding in different cosolvents. 40 Several studies have shown the effect of cosolvents including aqueous organic media, osmolytes and also different families of ILs on α-CT. 41−45 Despite numerous studies on stability and enzymatic activity of α-CT in various additives, the knowledge regarding the use of ILs with different numbers of cations per anion constant is scarce; moreover, the use of citrate anion for enzymatic stability is inadequate. Hence, meticulous research is needed to provide the understanding of the molecular mechanism for enzyme stability in vitro in the presence of ILs composed of cholinium cation and citrate anion.…”
Section: ■ Introductionmentioning
confidence: 99%